Suitability and realism of the novel Fix for Life cadaver model for videolaryngoscopy and fibreoptic tracheoscopy in airway management training - Michael W. van Emden; Jeroen J. G. Geurts; Patrick Schober; Lothar A. Schwarte (BMC Anesthesiology, 2020)
Abstract Background Videolaryngoscopy is increasingly advocated as the standard intubation technique, while fibreoptic intubation is broadly regarded as the ‘gold standard’ for difficult airways. Traditionally, the training of these techniques is on patients, though manikins, simulators and cadavers are also used, with their respective limitations. In this study, we investigated whether the novel ‘Fix for Life’ (F4L) cadaver model is a suitable and realistic model for the teaching of these two intubation techniques to novices in airway management. Methods Forty consultant anaesthetists and senior trainees were instructed to perform tracheal intubation with videolaryngoscopy and fibreoptic tracheoscopy in four F4L cadaver models. The primary outcome measure was the verbal rating scores (scale 1–10, higher scores indicate a better rating) for suitability and for realism of the F4L cadavers as training model for these techniques. Secondary outcomes included success rates of the procedures and the time to successful completion of the procedures. Results The mean verbal rating scores for suitability and realism for videolaryngoscopy was 8.3 (95% CI, 7.9–8.6) and 7.2 (95% CI, 6.7–7.6), respectively. For fibreoptic tracheoscopy, suitability was 8.2 (95% CI, 7.9–8.5) and realism 7.5 (95% CI, 7.1–7.8). In videolaryngoscopy, 100% of the procedures were successful. The mean (SD) time until successful tracheal intubation was 34.8 (30.9) s. For fibreoptic tracheoscopy, the success rate was 96.3%, with a mean time of 89.4 (80.1) s. Conclusions We conclude that the F4L cadaver model is a suitable and realistic model to train and teach tracheal intubation with videolaryngoscopy and fibreoptic tracheoscopy to novices in airway management training.